(untitled) (Ius Novum, 2026)
The commented ruling refers to the issue of the relationship between the provisions of Article 161 § 3 of the Penal Code and Article 165 § 1(1) of the Penal Code. The interpretative difficulties arose upon the introduction of Article 161 § 3 into the legal system as a consequence of the COVID-19 pandemic. The judicial authorities were faced with the choice of the correct legal classification of behaviours aimed at the spread of infectious diseases. The problem constituting the crux of the title judgment is therefore important both dogmatically and in the practice of applying the law. The significance of the subject matter is also visible in the special nature of the prohibited acts in question, the implementation of which is related to the occurrence of biological pathogens invisible to the human eye that cause infectious diseases and which did not disappear once the SARS-CoV-2 pandemic had been brought under control.